SHOULD I STAY OR SHOULD I GO? PERCEPTIONS OF SERBIAN EMIGRANT MEDICAL WORKERS IN GERMANY - Tintor, Sara (Srpski medicinski časopis Lekarske komore, 2025)
Background: Throughout history, various driving forces have influenced both forced and voluntary migrations of healthcare workers. Objective: This study aims to obtain new insights into the work activities of foreign doctors from the Western Balkans practicing medicine in Germany. Materials and methods: In 2023, a qualitative cross-sectional study was conducted to analyze physicians’ motivation for emigration from their home countries, their professional status development in Germany, the German legal system, and overall satisfaction of the physicians. Results: The main findings highlight better salaries for doctors abroad and no development opportunities in their home countries as the main reasons for emigration. Immigrant physicians were mainly satisfied with their professional status development in Germany, but less satisfied with the German legal system. Conclusion: Employing doctors from the Western Balkans can alleviate the burden on the German healthcare system caused by the significant shortage of skilled labor force.